2017
DOI: 10.1038/s41598-017-09387-8
|View full text |Cite
|
Sign up to set email alerts
|

Opposite feedback from mTORC1 to H-ras and K-ras4B downstream of SREBP1

Abstract: As a major growth factor transducer, Ras is an upstream activator of mTORC1, which further integrates nutrient and energy inputs. To ensure a contextual coupling of cell division via Ras/MAPK-signalling and growth via mTORC1-signalling, feedback loops from one pathway back to the other are required. Here we describe a novel feedback from mTORC1, which oppositely affects oncogenic H-ras- and K-ras-signalling output, and as a consequence stemness properties of tumourigenic cells. Amino acid stimulation of mTORC1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

6
3

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 66 publications
2
12
0
Order By: Relevance
“…The plasmids pmGFP-/mCherry-H-RasG12V and pmGFP-/mCherry-K-RasG12V were previously described [ 71 , 72 ]. pcDNA3.1-galectin-3 [ 38 ] was used for the overexpression of human galectin-3.…”
Section: Methodsmentioning
confidence: 99%
“…The plasmids pmGFP-/mCherry-H-RasG12V and pmGFP-/mCherry-K-RasG12V were previously described [ 71 , 72 ]. pcDNA3.1-galectin-3 [ 38 ] was used for the overexpression of human galectin-3.…”
Section: Methodsmentioning
confidence: 99%
“…After 24 h of treatment cells were fixed with 4% PFA for 12 min and mounted with Mowiol 4-88 (#81381; Sigma-Aldrich). The lifetime of the donor mGFP was measured using a fluorescence microscope (Zeiss AXIO Observer D1) with fluorescence lifetime imaging attachment from Lambert Instruments as previously described in (Guzmán et al, 2016 ; Posada et al, 2017) . At least 50 cells were selected to measure the lifetime in each sample.…”
Section: Methodsmentioning
confidence: 99%
“…Intriguingly, they also demonstrated that active H-RasG12V (but not its minimal membrane anchor tH) can negatively affect the pool of PS that is engaged by K-Ras, thus remotely downregulating K-Ras nanoclustering [37]. This intrinsic, negative feedback from active H-Ras to K-Ras may be highly significant for Ras biology, given that opposite regulation of these two Ras isoforms is also naturally implemented downstream of the mTORC1 pathway [38]. Hancock and Gorfe groups further demonstrated that the HVR of K-Ras adopts distinct conformational states that mediate specific engagements with asymmetric PS species with one saturated and one unsaturated acyl chain [39].…”
Section: Lipid Domains and Nanoclustermentioning
confidence: 98%